To find expressions that are equivalent to \( 2x^2 - 8x - 10 \) when distributed, we can simplify each option.
-
Option #1: \( 2x(x - 4x - 5) \)
Simplifying: \[ 2x(x - 4x - 5) = 2x(-3x - 5) = -6x^2 - 10x \] This does not match the original expression.
-
Option #2: \( (2x + 2)(x - 5) \)
Simplifying: \[ (2x + 2)(x - 5) = 2x^2 - 10x + 2x - 10 = 2x^2 - 8x - 10 \] This matches the original expression.
-
Option #3: \( 2x(x - 5) + 2(x - 5) \)
Simplifying: \[ 2x(x - 5) + 2(x - 5) = (2x + 2)(x - 5) = 2x^2 - 8x - 10 \] This also matches the original expression.
-
Option #4: \( (x - 5)(x - 3) \)
Simplifying: \[ (x - 5)(x - 3) = x^2 - 3x - 5x + 15 = x^2 - 8x + 15 \] This does not match the original expression.
-
Option #5: \( -6x - 10 \)
This expression is not quadratic and does not match the original expression.
Therefore, the options that match \( 2x^2 - 8x - 10 \) are Option #2 and Option #3.
So, the answer is:
Option #2 and Option #3.